How Comics Help to Teach Shakespeare in Schools - Maynard, The University of Adelaide, Australia, Amy Louise (Asiatic: IIUM Journal of English Language and Literature, 2013)
To address the literacy crisis that is currently affecting Britain, and to engage students inÂ English studies in Australia, teachers and educators are turning to graphic novels;Â specifically, graphic novel adaptations of Shakespeareâ€™s plays. Whilst there have beenÂ critics of this approach, teaching children about Shakespeare and poetry throughÂ comics appears to be successful. There have already been multiple examples of theÂ younger generation becoming familiar with Shakespeare through pop culture, andÂ graphic novels have the advantage in that they have been proven to improve literacyÂ rates. It is a belief of prominent Shakespearean scholars that the works of ShakespeareÂ should not be limited to the elite, as his themes, characters and most importantly,Â language, is universal, and can be interpreted in many different ways.